Reasoning with Zhuangzi. Issue 1 (5th November 2018) - Wenzel, Christian Helmut
Abstract: In this essay I closely look at dialogues from the Daoist text Zhuangzi and examine their modes of reasoning. The observations, comments, and dialogues are often witty, surprising, and puzzling. Sometimes they are mystic and difficult to understand. But how "reasonable" are the answers given in these dialogues? I will focus on a dialogue from chapter 17, called "Autumn Floods." I will closely follow and analyze the arguments and their twists. In particular, I will question the use of the word "Dao." I will also place this analysis in broader comparative frameworks regarding rationality, the Sapir‐Whorf hypothesis, and Western traditions.